2019
DOI: 10.1155/2019/8505382
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Excision of Intra-Articular Osteoid Osteoma at the Elbow

Abstract: Osteoid osteoma (OO) apparent in the intra-articular region of the elbow is very rare. Although computed tomography-guided excision and radiofrequency ablation have been recognized as useful treatment options, arthroscopic excision has recently received focus as an alternative strategy for lesions close to neurovascular structures or intra- and juxta-articular lesions. We herein report a 17-year-old female who underwent arthroscopic treatment for intra-articular OO located at the olecranon/coronoid fossa. Her … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…Osteoid osteoma of the elbow, in particular, has been reported to present as a monoarthritis with joint effusion, rather than the typical nocturnal pain responsive to NSAIDs [11,12]. Unsurprisingly, literature on this topic has described confusion of this entity with a variety of diagnoses such as lateral epicondylitis, osteochondral defect, hemophilic arthropathy, infection, and trauma [2][3][4][5]8,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Osteoid osteoma of the elbow, in particular, has been reported to present as a monoarthritis with joint effusion, rather than the typical nocturnal pain responsive to NSAIDs [11,12]. Unsurprisingly, literature on this topic has described confusion of this entity with a variety of diagnoses such as lateral epicondylitis, osteochondral defect, hemophilic arthropathy, infection, and trauma [2][3][4][5]8,13].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoid osteomas occur within the femur or tibia in 50% of cases, usually at the metaphyseal-diaphyseal junction [ 2 , 4 ]. However, presentation in nearly every bone has been reported [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-articular radiofrequency ablation can cause osteonecrosis or cartilage damage [ 3 , 8 ], while open surgery is associated with longer post-operative morbidity. Recently, various authors have reported arthroscopic excision of the lesion as a less invasive approach [ 12 ]. The direct magnified vision under arthroscope, the option to perform further maneuverers such as synovial biopsy/debridement and capsular releases to improve ROM are additional advantages.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of arthroscopy is reduced postoperative pain related to minimal incisions, fewer wound problems, wider intraoperative vision, a less invasive surgery, and earlier return to full activity levels [13]. To the best of our knowledge, 19 cases in 1 case series and 8 case reports describe arthroscopic resection for OO in the elbow [8,[19][20][21][22][23][24][25][26]. Six patients with OO in the olecranon fossa are among these cases.…”
mentioning
confidence: 99%